A dose response relationship between accelerometer assessed daily steps and depressive symptoms in older adults: a two-year cohort study. (25th September 2020) - Hsueh, Ming-Chun; Stubbs, Brendon; Lai, Yun-Ju; Sun, Chi-Kuang; Chen, Li-Jung; Ku, Po-Wen
Abstract: Objectives: this study investigated the prospective associations of accelerometer assessed daily steps with subsequent depressive symptoms in older adults. Methods: a 2-year prospective study was performed in the community. A total of 285 older adults ≥65 years (mean age = 74.5) attended the baseline assessment in 2012. The second wave of assessment was carried out in 2014 including 274 (96.1%) participants. Daily step counts were measured with a triaxial accelerometer (ActiGraph GT3X+), and participants were divided into three categories (<3, 500, 3, 500–6, 999 and ≥ 7, 000 steps/day). The 15-item Geriatric Depression Scale was used to measure depressive symptoms. Negative binomial regression models with multivariable adjustment for covariates (baseline depressive symptoms, accelerometer wear time, age, gender, education, chronic disease, activities of daily living) were conducted to examine the association between daily steps and subsequent depressive symptoms. Results: each 1, 000-step increase in daily walking was linearly associated with a reduced rate of subsequent depressive symptoms (rate ratio [RR] = 0.95, 95% confidence interval [CI] = 0.92–0.98). Participants with daily step count in 3, 500–6, 999 (RR = 0.84, 95% CI = 0.70–0.99) and ≥7, 000 steps (RR = 0.71, 95% CI = 0.55–0.92) per day had fewer depressive symptoms at follow-up. Sensitivity analyses assessing confounding and reverse causation provided further support for the stability of our findings. Conclusion: older adults engaging in more daily steps had fewer depressive symptoms after 2 years. Even as few as 3, 500–6, 999 steps a day was associated with a protecting effect. Accumulating ≥7, 000 steps a day could provide the greatest protection against depressive symptoms.